2016
DOI: 10.1007/s00382-016-3407-x
|View full text |Cite
|
Sign up to set email alerts
|

Climate model forecast biases assessed with a perturbed physics ensemble

Abstract: initialised climate model forecasts by reducing model biases through regional adjustments to physical processes, either by tuning or targeted parametrisation refinement. Further, such regionally tuned models might also significantly outperform standard climate models, with global parameter configurations, in longer-term climate studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…By design, such statistical approaches inherently assume that the key drivers are meteorological and neglect feedback with, for example, the biosphere, that can be included in more specialized ESMs; for example, Coupled Chemistry Models. The power of LEs-even without additional complexity-as tools to investigate mean state biases 77 and extreme events, as well as their impacts on ecosystems, food security and public health, remains largely unexplored.…”
Section: Emerging Earth System Applicationsmentioning
confidence: 99%
“…By design, such statistical approaches inherently assume that the key drivers are meteorological and neglect feedback with, for example, the biosphere, that can be included in more specialized ESMs; for example, Coupled Chemistry Models. The power of LEs-even without additional complexity-as tools to investigate mean state biases 77 and extreme events, as well as their impacts on ecosystems, food security and public health, remains largely unexplored.…”
Section: Emerging Earth System Applicationsmentioning
confidence: 99%
“…For the emulator, a two-layer feed-forward artificial neural network (ANN; Knutti et al, 2003;Sanderson et al, 2008a;Mulholland et al, 2017) was used. Although other machinelearning algorithms could be suitable (Rougier et al, 2009;Neelin et al, 2010;Bellprat et al, 2012aBellprat et al, , b, 2016, we chose an ANN because it permits multiple simultaneous emulator targets (i.e., TOA SW and LW at the same time).…”
Section: Discussionmentioning
confidence: 99%
“…The studies span a range of topics, from the earlier studies focusing on climate sensitivity (e.g., Murphy et al, 2004;Stainforth et al, 2005;Sanderson et al, 2008aSanderson et al, , b, 2010Sanderson, 2011), to later ones attempting to generate plausible representations of the climate without flux adjustments (e.g., Irvine et al, 2013;Yamazaki et al, 2013) and using history matching to reduce parameter space uncertainty . More recently, Mulholland et al (2017) demonstrated the potential of using PPEs to improve the skill of initialized climate model forecasts with 1-month lead time, and Sparrow et al (2016) showed that large PPEs can be used to identify subgrid-scale parameter settings that are capable of best simulating the ocean state over the recent past . However, very little (Bellprat et al, 2012b(Bellprat et al, , 2016 has been published on using PPEs for parameter refinement with the aim of improving regional climate models (RCMs).…”
Section: Introductionmentioning
confidence: 99%
“…The second is simulation bias reduction methods through perturbed parameter studies (e.g. Hawkins et al, 2019;Li et al, 2019;Mulholland et al, 2017). The third category is extreme weather event attribution studies where quantitative assessments are made of the change in likelihood of extreme weather events occurring between past, present and possible future climates (e.g.…”
Section: Introductionmentioning
confidence: 99%